The Impact of Spiritual and Religious Activities on the Well-being and Academic Achievement of the College students at San Sebastian College Recoletos de Cavite - Quirante, Mark Joseph; Avila, Marianne (JPAIR Multidisciplinary Research, 2025)
This study investigates the influence of spiritual and religious activities on the well-being and academic success of college students at San Sebastian College Recoletos de Cavite, aiming to address existing gaps in understanding within diverse cultural and religious contexts like the Philippines. Utilizing a quantitative approach, data from 350 randomly selected students were analyzed, revealing a minimal positive linear correlation between engagement in religious activities and overall well-being, alongside a negligible linear relationship with academic performance. ANOVA findings underscored significant variations in impact across different academic disciplines, emphasizing the need for tailored interventions to support students’ holistic development. The results suggest a limited association between engagement in religious activities and student outcomes, prompting further research to explore the roles of spirituality and religious engagement in enhancing student well-being and academic success.